Factors leading to goal scoring in the Spanish and Italian soccer leagues - Papadopoulos, S.; Papadimitriou, K.; Konstantinidou, X.; Matsouka, O.; Pafis, G.; Papadopoulos, D. (SportMont, 2021)
The purpose of this study was to analyse the goal-scoring attacks made by the top four teams in the final standings of the Spanish and Italian 2017-2018 Football League tables. One of the objectives of the study was to compare the match behaviours leading to goal scoring, demonstrated by the aforementioned teams. The sample of the study comprised 606 goals, 316 scored in the Spanish League and 290 in the Italian League, and 280 matches. The phases were recorded using the SportScout coaching tool. The studied parameters were: time frame in which the goals were scored, type of final attempt, type of play that resulted in a goal, type of attack, mode of set play, goal-scoring zone, zone of the final pass, starting zone of the attack, and number of passes. The data were statistically processed using the Crosstabs analysis and the Chi-square significance test. The results showed that the two leagues differed in the type of attack and in the offensive zone. The observed differences were possibly due to the different approach to the game in the two leagues, with the Spanish teams relying more on organized combination play, while the Italians showed a greater diversity in their offensive play.